Process writing and its effectiveness in improving writing skills of year 5 pupils of Sek. Keb. Bukit Kenak, Jertih / Wan Rohani Wan Sulong - Wan Sulong, Wan Rohani (2002)
Process Writing is one of the effective strategies used in teaching writing skills, the purpose of this study is to overcome the difficulties facing by year 5 pupils in writing skills using Process Writing. By using the step by step process, the pupils will be able to organize their ideas before transferring the ideas into a good piece of work. This study involved 30 year 5 pupils of Sekolah Kebangsaan Bukit Kenak, Jertih. Data was obtained by using questionnaires and also a classroom observation on pupils' reactions. The questionnaires were distributed after two lessons were conducted. The pupils showed some improvement after some written activities were given to them. The results showed that Process Writing is effective to improve pupils' writing skills. The findings too proved that the pupils were motivated and interested in writing activities based on observation by the teacher.